Post-whitening adhesion and time intervals: a topic review - Domínguez, John Alexis; Fortes-Bittencourt, Bruna; Mongruel-Gomes, Osnara María; Scholz, Nelson (Revista Facultad de Odontología Universidad de Antioquia, 2013)
Despite the enormous clinical success of dental whitening procedures, not all the questions about their use have been fully explained, especially in relation to the adverse effects on bond strength of adhesive restorations in enamel and dentin, which still remain controversial. This topic review pretends to analyze some of the issues on the interaction between post-whitening adhesion and the treatments to control such interactions. Based on the revised literature, we may conclude that a time delay of at least 7 days between whitening and the restorative procedure is advisable, so that all the remaining residual oxygen can be released from the tooth structure and, where necessary, immediately restore the whitening process, using an antioxidant such as 10% sodium ascorbate (as a gel) is a viable alternative to reduce the effects of whitening on the adhesive process.